2011
DOI: 10.1590/s0103-21002011000500016
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de escalas de avaliação de risco para úlcera por pressão em pacientes em estado crítico

Abstract: Objective: To compare the Norton, Braden and Waterlow scales of risk for pressure ulcer in critically ill patients. Methods: An exploratory and longitudinal study covering 42 patients who were evaluated for 15 days or at least 10 consecutive days, in three intensive care units within Fortaleza, Brazil, from March to July 2009. Each patient was evaluated, simultaneously, by three nurses, each of whom was responsible for the application of only one of the scales. Results: There was a 59.5% incidence of ulcers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
0
32

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 28 publications
6
17
0
32
Order By: Relevance
“…26,[28][29] In a descriptive exploratory study 20 with 14 adults of both sexes found predominance of risk in females corroborates another study that also showed similar incidence. 18 However, points up the limitation of the small sample size and may lead to bias result.…”
Section: Assessment Of Risk For Pressure Ulcers…supporting
confidence: 80%
See 3 more Smart Citations
“…26,[28][29] In a descriptive exploratory study 20 with 14 adults of both sexes found predominance of risk in females corroborates another study that also showed similar incidence. 18 However, points up the limitation of the small sample size and may lead to bias result.…”
Section: Assessment Of Risk For Pressure Ulcers…supporting
confidence: 80%
“…Moreover, the transfer of the operating table to the stretcher recovery room after anesthesia can trigger friction and shear forces, and is considered a risk factor. 18 Regarding the hospitalization period , there was media development PU ranged from 8 to 40 days 18,20 , corroborating other in which the average time was 9,6 days (DP± 3,3) 24,26 and 18,43 days (p 0,015) 18 ICU aimed at decision-making regarding the prevention and possible treatment. Among these there are the scales used in the articles analyzed as described in Table 3.…”
Section: Assessment Of Risk For Pressure Ulcers…supporting
confidence: 68%
See 2 more Smart Citations
“…Os principais fatores de risco descritos na literatura são a mobilidade prejudicada, desnutrição e baixo índice de massa corporal (IMC), problemas de saúde física, incluindo os que afetam a oxigenação e perfusão, idade avançada, temperatura corporal, fricção e cisalhamento, umidade da pele, dificuldades cognitivas e de percepção sensorial (ARAÚJO; MOREIRA; CAETANO, 2011;POSS et al, 2010).…”
Section: Introductionunclassified